2011
DOI: 10.1016/j.intmar.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Herding Behavior in Peer-to-Peer Loan Auctions

Abstract: Online Peer-to-Peer (P2P) loan auctions enable individual consumers to borrow and lend money directly to one another. We study herding behavior, defined as a greater likelihood of bidding in auctions with more existing bids, in P2P loan auctions on Prosper.com . The results of an empirical study provide evidence of strategic herding behavior by lenders such that they have a greater likelihood of bidding on an auction with more bids (a 1% increase in the number of bids increases the likelihood of an additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(206 citation statements)
references
References 21 publications
4
196
3
3
Order By: Relevance
“…In cooperation with crowdfunding platforms, for example, it would be possible to employ larger n analyses of crowdfunding characteristics and successes (e.g. Herzenstein et al, 2011). Future studies should also take additional explanatory factors into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cooperation with crowdfunding platforms, for example, it would be possible to employ larger n analyses of crowdfunding characteristics and successes (e.g. Herzenstein et al, 2011). Future studies should also take additional explanatory factors into account.…”
Section: Discussionmentioning
confidence: 99%
“…They could include additional information about the researchers which is publicly available, such as their Facebook or Twitter profiles or networks (Byrnes et al, 2014; Lin et al, 2013), the concrete payment mechanisms of crowdfunding platforms (Cumming et al, 2015), or the “herding behavior” that has been shown among donors, making donations more likely if others have donated before (Agrawal et al, 2013: 4f. ; Herzenstein et al, 2011). As STEM projects are dominant on crowdfunding platforms, it would also be interesting to analyze for each discipline seperately if different factors are influential for the success of a project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 We do not differentiate between the different stages of the auction in the empirical model, because including a dummy variable for the third stage of the auction alongside interaction terms of this dummy with the funding share, the funding goal, and the funding limit neither generates significant estimates nor changes the results of the other explanatory variables. also been observed in crowdlending (Herzenstein et al 2011;Lee and Lee 2012) and equity crowdfunding (Hornuf and Schwienbacher 2015;Vismara 2015). To test whether herding affects the pricing of cash flow rights on Innovestment, we include the sum of investment bids in a start-up that were made earlier on the same day, as additional explanatory variable.…”
Section: Herdingmentioning
confidence: 99%
“…Herzenstein, Dholakia and Andrews (2011) found that the herding effect is persistent and decreasing according to the data of Prosper platform [5]. found that investors have a certain risk identification ability and can identify different default risks behind the same in-C. M. Lu, L. Zhang American Journal of Industrial and Business Management terest rate through the borrower information [6].…”
Section: Research On Investorsmentioning
confidence: 99%